Modeling of imidization kinetics - Seo, YS (SOC PLASTICS ENG INC, 1997)
We investigated the applicability of a new kinetic model to the polyamic acid imidization process, which has been generally represented as involving two steps, fast and slow, with specific rate constants due to the existence of kinetically nonequivalent amic acid states. A time dependent nonlinear function of the form sech(-at) for the rate expression allowed us to simulate the general features of the imidization process. in the early stage, it is almost a constant, in accordance with the process of imidization of highly active amic acid groups, which is eventually limited by the chemical conversion of amic acid groups into imide rings. In the final stage, the reaction rate decreases exponentially because it is controlled by the conversion rate of amic acid groups from inactive to active states, Overall reaction rate is determined by the change in the rate-determining stage, and thus eventually exhibits a sharp drop in reaction rate. Comparison showed good agreement with experimental data. Activation energies calculated from the new model were in good agreement with those obtained from the first order model. The applicability of the model was further assessed by modeling a process involving two separate imidization processes, Simulation results showed good quantitative and qualitative correlations with experimental data. The model is also in good agreement with another complicated model.